PENDAMPINGAN COMMUNITY BASED DEVELOPMENT UNTUK PENGEMBANGAN POTENSI EKOWISATA PANTAI CEMORO SEWU PUGER KULON - Eka Bambang Gusminto; Didik Pudjo Musmedi; Vanya Pinkan Maridelana; Tria Putri Noviasari; Alfina Widi Safitri (Jurnal Abdimas Bina Bangsa, 2023)
Tourism is among the key sectors that drive economic growth in a region, including the Jember Regency. Puger Kulon Village, which is part of Jember Regency, has potential as a tourist destination due to its location on the south coast of East Java. Puger Kulon Village has a newly-operated beach opened at the end of 2021, namely Cemoro Sewu Beach. Currently, Cemoro Sewu Beach's management is not optimal and its ecotourism potential has not been fully explored. In order to make Cemoro Sewu Beach a leading ecotourism site in Jember Regency, institutional strengthening and mentoring activities involving community participation are conducted. The activities also include socialization and consutations through Frocus Group Discussions (FGD) to increase the professionalism of managers, management practices that are in accordance with ecotourism principles, and infrastructure to support the marketing of Cemoro Sewu Beach as a tourist destination